Firms and workers : who fails in times of crisis? - Ferreira, Priscila (2011)
Using a panel of linked employer-employee data from Portugal, we follow the performance of firms and workers during the first decade of 2000s in terms of the risk of firm shutdown and of chances of workers’ entering unemployment. This allows us to identify the characteristics of unsuccessful firms and workers over this period and, of most interest, whether these characteristics changed as a consequence of the global crisis. In addition, and different from previous works, we (i) assess whether there is a differential effect to crisis depending on firm size, and (ii) relate the workers’ risk of unemployment to the hazard of firm shutdown. In the analyses of hazard of shutdown and risk of unemployment most of the effects of observed covariates remained unchanged through the business cycle. There is a differential response to crisis depending on firm size. A small firm’s risk of shutdown is 9 times the risk of a large firm. However, the chances of becoming unemployed are less than twice larger for a worker in a small firm. This suggests that large firms may be less likely to shutdown, but they are not a shield from unemployment.